Re-Branding dan Perancangan Promosi untuk Clothing Maker-Garmen di Malang - Callista Ignacia; Etsa Astridya Setiyati; Ayyub Anshari Sukmaraga (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2021)
In beginning and building on a business, brand name and product quality are important things to note. Therefore, with branding or re-branding can be a limitation and differentiator of each business actor. Besides promotional media design is also very helpful in increasing awareness. Design object in this Final Project is Clothing Maker-Garmen in Malang. Clothing Maker-Garmen is one of the small and medium business working at clothes convection. Since established in 2014 Clothing Maker-Garmen has not been widely known by the public. Therefore, it is necessary to re-branding in order to increase brand awareness and business income. The resulting media are logo (positive and negative), tagline, corporate identity (letterhead, envelope, seal, payment note), graphic standart manual (GSM), as well as promotional media such as brochures, business cards, catalog books and merchandises. The method used is qualitative-descriptive and data retrieval is done through the process of interview (in depth interview) and book-related study. Data analysis used in re-branding and promotion design is Segmentation, Targeting and Positioning (STP). The design used in the form of media design and creative design. The result of re-branding design obtained in the form of increased brand awareness that hit or effect on increasing the number of person and business income.